Decreased Excretion of Urinary Exosomal Aquaporin-2 in a Puromycin Aminonucleoside-Induced Nephrotic Syndrome Model - Abdeen, Ahmed (Int J Mol Sci, 2020)
Urinary exosomes, small extracellular vesicles present in urine, are secreted from all types of renal epithelial cells. Aquaporin-2 (AQP2), a vasopressin-regulated water channel protein, is known to be selectively excreted into the urine through exosomes (UE-AQP2), and its renal expression is decreased in nephrotic syndrome. However, it is still unclear whether excretion of UE-AQP2 is altered in nephrotic syndrome. In this study, we examined the excretion of UE-AQP2 in an experimental rat model of nephrotic syndrome induced by the administration of puromycin aminonucleoside (PAN). Rats were assigned to two groups: a control group administered saline and a PAN group given a single intraperitoneal injection of PAN (125 mg/kg) at day 0. The experiment was continued for 8 days, and samples of urine, blood, and tissue were collected on days 2, 5, and 8. The blood and urine parameters revealed that PAN induced nephrotic syndrome on days 5 and 8, and decreases in the excretion of UE-AQP2 were detected on days 2 through 8 in the PAN group. Immunohistochemistry showed that the renal expression of AQP2 was decreased on days 5 and 8. The release of exosomal marker proteins into the urine through UEs was decreased on day 5 and increased on day 8. These data suggest that UE-AQP2 is decreased in PAN-induced nephrotic syndrome and that this reflects its renal expression in the marked proteinuria phase after PAN treatment.